Critical evaluation of Acordada No. 281 of the Superior Court La Rioja. The role of psychological reports in the Gesell Chamber (Papeles, 2024)
The regulation of the Gesell Chamber (hereinafter GC) system in the criminal procedural legislation of the province of La Rioja has two shortcomings: 1) Lack of systematisation in its regulation and, consequently, 2) Denial of the special vulnerability of children and adolescents (hereinafter BGTY) victims or witnesses of crimes who must testify through this procedure. Both weaknesses hinder the proper use of this tool and at the same time especially affect the rights of children and adolescents who must go through a judicial procedure -especially in the face of events that affect their sexual integrity-. This article will address the second of the hortcomings, caused by the issuance of Resolution No. 281 of the High Court of Justice of La Rioja (hereinafter TSJ).
Keywords: Gesell Chamber; Boys, Girls and Adolescents; psychological report; Memory; criminal procedural law